A cluster of CYP6 gene family associated with the major quantitative trait locus is responsible for the pyrethroid resistance in Culex pipiens pallen. Issue 4 (11th March 2019) - Zou, F.; Guo, Q.; Shen, B.; Zhu, C.
Abstract: The emergence and rapid spread of insecticide resistance in several mosquito species has become a significant obstacle in management of mosquito‐borne diseases, including deltamethrin resistance in Culex pipiens pallens . Previous study identified a major deltamethrin resistance quantitative trait locus (DR‐6) that alone explained 62% of the genetic variance. In this study, the marker L4B1.102 and L4B1.175 associated with the DR‐6 were characterized. We searched for potential candidate genes in the flank region of two markers in the genome sequence and showed that a cluster of CYP6 cytochrome P450 genes ( CYP6BB4, CYP6BB3, CYP6CC2, CYP6P14, CYP6BZ2, CYP6AA9, CYP6AA8, CYP6AA7 ) was in the vicinity of DR‐6. Significant differences in the expression of these P450s in the larval and adult stages were identified in the resistant strains compared with the susceptible strain. For CYP6AA9 and CYP6BB4, the correlation analysis showed a highly positive correlation between relative gene expression quantification and the resistance level in different strains. Knockdown of CYP6BB4 increased the sensitivity of mosquitoes to deltamethrin. We identified that the deltamethrin resistance was in a cluster of CYP6 genes in C. pipiens pallens, and CYP6BB4 may play a significant role in the development of deltamethrin resistance.